Interaction force mechanism for the improvement of reclaimed soil aggregate stability in abandoned homestead by different organic-inorganic soil conditioners - Liu, Zhe; Zhang, Yang; Sun, Yingying; Li, Xuxiang; Wang, Na; Wang, Xue; Meng, Tingting (Frontiers in Environmental Science, 2023)
Reasonable application of organic-inorganic soil conditioners can effectively improve the structure and fertility of reclaimed soil in abandoned homestead. Aggregate stability is an important indicator to evaluate soil structure and fertility, and is largely influenced by soil internal forces (van der Waals attractive force, electrostatic repulsive force, hydration repulsive force) and particle surface properties. However, there are few studies on the influence of different soil conditioners on the reclaimed soil internal forces and its relationship with the aggregate stability. Therefore, we selected six different treatments of organic fertilizer (TO), fly ash (TF), maturing agent (TM), maturing agent + organic fertilizer (TMO), fly ash + organic fertilizer (TFO) and control (CK) to conduct a five-year field experiment to study the effects of reclaimed soil particle interaction forces and surface characteristics on aggregate stability under the treatment of different soil conditioners. The results showed that with the application of soil conditioners, the soil organic matter (SOM), specific surface area (SSA), surface charge (σ 0 ), cation exchange capacity (CEC), aggregate mean weight diameter (MWD) and Hamaker constant increased gradually, while the pH value decreased slightly. In particular, the MWD under the treatments of TFO and TMO increased by 150.3% and 65.6% respectively compared with that under the CK treatment. With the increasing application of soil conditioners, the electrostatic repulsive force and van der Waals attractive force between reclaimed soil particles increased constantly, but the net resultant force between particles decreased and the net attractive force increased continuously, thus improving the aggregate stability. Therefore, there is a significant negative correlation between the net resultant force among reclaimed soil particles and MWD & CEC. In addition, 10 -2 mol L -1 is the critical concentration that affects the 删除的内容: Organic-inorganic